Тext Understanding as a Special Kind of Understanding - Nataliia Akimova; Alina Akimova (Психолінгвістика, 2018)
The analysis of modern theories of text understanding are presented in the article. Different theoretical methods and techniques were used for this purpose: deductive and inductive methods, analysis and synthesis, generalization, systematization and modeling as well as some interpretive methods that are based on specific principles of systemic, activity, cognitive and organizational approaches. The author notes that six approaches to the interpretation of understanding can beaccented in modern psychological literature. They are understanding as knowledge, understanding as comprehension, understanding as interpretation, understanding as a process of solving tasks, understanding as the inclusion of new knowledge in the subject's experience, understanding as awareness. But only four of them are used to understand the text. The conclusion is made as a result of systematization of the achievements of these approaches. It is concluded that the process of text understanding is a complex process that occurs at several levels: from the simplest to perception, through interpretation (thinking and memory), to a higher level that is consciousness, where emotional identification and awareness are presented. As a result of understanding someorganized ideas about the text (model, conclusions, mental representation) appear in the mind of the subject. Next they recieve the verbal form and objectify as a secondary text (received from the recipient as a reaction to the read text), that represented concept or secondary meanings. The process and the result of text understanding depend on some subjective factors (the recipient experience (apperception), subjective state at the time of reception, the cultural and historical context) and some objective factors (textual or semantic dominants). Context forms not only preliminary expectations, but also verifies the final result of understanding. It is anew secondary meanings, that accord with already existing senses in the mind. Thus the semantic level of reader consciousness enrich and reorganize, that are represented as change in behavior.